Optimized nitrogen fertilizer management enhances soybean (Glycine max (L.) Merril.) yield and nitrogen use efficiency by promoting symbiotic nitrogen fixation capacity - Xu, Yaxin; Gao, Quantong; Xue, Lihua; Zhang, Jianxin; Wang, Cong (Frontiers in Plant Science, 2025)
IntroductionAlthough the mulched drip irrigation system combined with high nitrogen input (240∼310 kg ha-1) in Xinjiang, China, frequently achieves record-high soybean yields (6855 kg ha-1), this practice is not conducive to symbiotic nitrogen fixation and compromises agricultural sustainability.MethodsUnder the mulched drip irrigation, this study evaluation four nitrogen application treatments (N0: 0 kg ha-1, N120: 120 kg ha-1, N180: 180 kg ha-1, and N240: 240 kg ha-1) were evaluated over two consecutive growing seasons to investigate their effects on nodule morphological and physiological traits, stem ureide content, and the percentage of nitrogen derived from the atmosphere (%Ndfa) during the reproductive growth stage. ResultsThe application of 180 kg ha-1 nitrogen significantly increased nodule number, nodule dry weight, nodule sucrose content, and nodule starch content, while improving soybean yield and nitrogen agronomic use efficiency. Conversely, the application of nitrogen exceeding 180 kg ha-1 inhibited nitrogenase activity, suppressed leghemoglobin synthesis, disrupted the glutamine synthetase/glutamate synthase metabolic pathway, and reduced ureide translocation from nodules to stems, leading to significant accumulation of ureides in nodules. Correlation and path analyses indicated that nitrogenase activity, leghemoglobin content, urate oxidase activity, and stem ureide content were significantly positively correlated with %Ndfa, whereas nodule ureide content showed a significant negative correlation with %Ndfa. Stem ureide content exhibited a strong direct positive effect on %Ndfa (path coefficient = 0.95), confirming its validity as a robust indicator for assessing SNF capacity. DiscussionIn conclusion, mulched drip irrigation, applying 180 kg ha-1 nitrogen at the beginning pod stage (R3) effectively enhances root nodulation, promotes carbohydrate allocation to nodules, sustains symbiotic nitrogen fixation activity, and ultimately increases soybean yield and nitrogen use efficiency. Thus, under mulched drip irrigation system, applying the correct rate of nitrogen fertilizer is beneficial for enhancing soybean yield and mitigating environmental risks, which holds significant importance for promoting sustainable agricultural development.